Effect of microhabitat distribution and substrate roughness on barnacle Tetraclita stalactifera (Lamarck, 1818) settlement - Skinner,Luís Felipe (2005)
Studies were carried out on microhabitat distribution and substrate roughness on barnacle settlement at Cabo Frio region, Rio de Janeiro, Brazil. Ten commercial blocks of granite rock (100 cm²) were attached to rocky coast at 0.6 tide level (5 smooth blocks and 5 rough with 20 holes). Experiment was conduced for five weeks, with repetitions each week. Settlement was higher on rough (398 individuals) than on smooth blocks (38 individuals) on the same week. There was no significant difference between settlement in the centre of the block and at the edge. Significant differences observed among weeks were affected by the variability of cyprid larvae density. This result showed that roughness was an important variable to be considered on barnacle settlement.